Efecto antifúngico “in vitro” de la miel de apis mellifera l. en hongos ambientales (mohos) y dermatofitos patógenos - Sánchez Muguerza, Leidy Verónica (2009)
The present work was aimed at determining the antifungal effect in vitro of Apis mellifera L. honey versus environmental fungi (Aspergillus sp., Penicillium sp.) Pathogens and dermatophytes (Epidermophyton floccosum, Microsporum canis and Trichophyton rubrum), cutaneous mycoses are among the significant prevalence of infections in the world, and also determine the chemical composition of honey samples in order to establish ranges of values of some of its main components such as sugars, acidity, moisture and pH indicating its microbial stability. In Chemical Testing was determined pH, acidity, concentration of sugars and humidity values that are within the ranges established. For the antifungal effect in vitro using the disk diffusion method - method of Kirby - Bauer, which made use of two samples of honey from different places of origin, who were identified as (A and B). Was submitted to the control groups (fluconazole, itraconazole and clotrimazole) and problem (honey "A" Honey "B") on each plate from the selected microorganism (fungi or dermatophytes environmental pathogens) and in the Sabouraud dextrose agar with chloramphenicol . The results were evidenced by measuring ruler with millimeter diameters of the zone of antifungal inhibition of growth of each disc and sensitivity for each organism, we also conducted a photographic control, concluded that the honey has a lower antifungal effect in vitro on cultures of Aspergillus spp. and ssp Penicillum versus Fluconazole and enhanced antifungal effect against Clotrimazole also has lower antifungal effect in vitro on cultures of Epidermophyton floccosum, compared with fluconazole and itraconazole, but higher antifungal effect against Clotrimazole and finally the honey bee has higher antifungal effect in vitro on cultures of Microsporum canis and Trichophyton rubrum, compared to itraconazole, fluconazole and clotrimazole